'First, do no harm': are disability assessments associated with adverse trends in mental health? A longitudinal ecological study. Issue 4 (16th November 2015) - Barr, B; Taylor-Robinson, D; Stuckler, D; Loopstra, R; Reeves, A; Whitehead, M
Abstract : Background: In England between 2010 and 2013, just over one million recipients of the main out-of-work disability benefit had their eligibility reassessed using a new functional checklist—the Work Capability Assessment. Doctors and disability rights organisations have raised concerns that this has had an adverse effect on the mental health of claimants, but there are no population level studies exploring the health effects of this or similar policies. Method: We used multivariable regression to investigate whether variation in the trend in reassessments in each of 149 local authorities in England was associated with differences in local trends in suicides, self-reported mental health problems and antidepressant prescribing rates, while adjusting for baseline conditions and trends in other factors known to influence mental ill-health. Results: Each additional 10 000 people reassessed in each area was associated with an additional 6 suicides (95% CI 2 to 9), 2700 cases of reported mental health problems (95% CI 548 to 4840), and the prescribing of an additional 7020 antidepressant items (95% CI 3930 to 10100). The reassessment process was associated with the greatest increases in these adverse mental health outcomes in the most deprived areas of the country, widening health inequalities. Conclusions: The programme of reassessing people on disability benefits using the Work Capability Assessment was independently associated with an increase in suicides, self-reported mental health problems and antidepressant prescribing. This policy may have had serious adverse consequences for mental health in England, which could outweigh any benefits that arise from moving people off disability benefits.